2012
DOI: 10.1073/pnas.1209192109
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclooxygenase-1, not cyclooxygenase-2, is responsible for physiological production of prostacyclin in the cardiovascular system

Abstract: Prostacyclin is an antithrombotic hormone produced by the endothelium, whose production is dependent on cyclooxygenase (COX) enzymes of which two isoforms exist. It is widely believed that COX-2 drives prostacyclin production and that this explains the cardiovascular toxicity associated with COX-2 inhibition, yet the evidence for this relies on indirect evidence from urinary metabolites. Here we have used a range of experimental approaches to explore which isoform drives the production of prostacyclin in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
136
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 41 publications
20
136
0
5
Order By: Relevance
“…Subsequently, we confirmed that PGIM was markedly suppressed by global deletion or inhibition of COX-2 in mice, consistent with results of Kirkby et al (1). However, the authors claimed PGIM is not reflective of vascular PGI 2 , reporting that infusion of a vascular stimulant, bradykinin, evokes COX-1-derived immunoreactive 6-keto PGF 1α , but not PGIM, in mice.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Subsequently, we confirmed that PGIM was markedly suppressed by global deletion or inhibition of COX-2 in mice, consistent with results of Kirkby et al (1). However, the authors claimed PGIM is not reflective of vascular PGI 2 , reporting that infusion of a vascular stimulant, bradykinin, evokes COX-1-derived immunoreactive 6-keto PGF 1α , but not PGIM, in mice.…”
supporting
confidence: 80%
“…Kirkby et al (1) failed to mention that deletion of COX-2 in vascular, smooth muscle cells, or both depressed urinary PGIM, providing direct genetic evidence for the role of vascular COX-2 in PGI 2 production (5). They also ignored the functional consequences of vascular deletion of COX-2, a predisposition to thrombosis and hypertension, or that urinary PGIM (alone among the major metabolites of PGs was suppressed in these mutants) inversely correlated with the rise in blood pressure (5), consistent with the hypothesis that the hypertensive phenotype is a consequence of disruption of COX-2-dependent formation of PGI 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There are two COX isoforms: COX-1 and COX-2. COX-1 is a constitutive, housekeeping enzyme that is ubiquitously expressed and is responsible for prostanoid production in most tissues (1). In contrast, COX-2 is an inducible enzyme, expressed at sites of inflammation, infection, and cancer (2) that generates prostanoids that drive disease pathogenesis.…”
mentioning
confidence: 99%